Navigating educational excellence: The implementation and impact of strategic management in a rural Islamic boarding school context - Arif Fajar; Rina Mida Hayati; Wawan Wawan; Subandi Subandi (Kuras Institute, 2026)
Purpose – This study aims to analyze the implementation of strategic management in improving the quality of education at Pondok Pesantren Nurul Fattah Tulang Bawang, including environmental analysis, strategy formulation, strategy implementation, as well as evaluation and control. Method – This study employs a qualitative approach using a field research design. Data were collected through observation, semi-structured interviews, and documentation. The research informants consisted of the pesantren leader, the head of the madrasah, and the boarding school administrators. Data analysis was conducted using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. To ensure the validity of the data, triangulation techniques were applied, including source triangulation, methodological triangulation, and time triangulation. Findings – The research findings indicate that the implementation of strategic management, from a conceptual standpoint, has encompassed all the key stages. However, its execution has not yet reached an optimal level. Environmental analysis is still conducted in an unsystematic manner, strategy formulation is not entirely data-driven, and the implementation phase is hindered by low levels of discipline and weak coordination. Furthermore, the evaluation process tends to focus more on the execution of activities rather than on the achievement of strategic objectives.